FITUR AKUSTIK PADA POLA INTONASI ANAK AUTISM SPECTRUM DISORDER DAN KONTROL MENGGUNAKAN FONETIK EKSPERIMENTAL (Measurement of Acoustic Features on Intonation Pattern in Children with Autism Spectrum Disorder and Control Using Experimental Phonetics) - Tri Wahyu Retno Ningsih (SAWERIGADING, 2022)
This study aimed to analyze prosodic elements of speech segments of children with Autism Spectrum Disorders (ASD) and compare with the control group (typical development children); 9-10 years  old.. The instrument of the research was used as script, which contains interrogative and declarative sentences. Data were analyzed using the PRAAT software. The acoustic features of the measured are the value F0, the mean value of F0, the initial pitch, the pitch range, the final pitch, and the temporal aspect. The results showed that acoustic measures in speech produced by ASD children tend to vary so that it is difficult to establish intonation patterns. The children produce intonation patterns with sloping contours in declarative and interrogative sentences, and tend to make the final pitch lengthening so that speech tends to show inclination patterns. The dominant variation occurs in the initial F0, there is a tendency for the initial F0 production to be higher compared to the second pitch.  Although the intonation patterns of ASD and typical development are different, there is a tendency for the same pattern, namely the lengthening of the pitch in the final speech which has an impact on increasing the total duration or temporal aspect.